Strategi Manajemen Konflik Antara Orang Tua Dengan Anak Remaja Yang Mengalami Masalah Keterbukaan Diri Di Desa Grenden Kecamatan Puger - Hailiyah, Ida Haitul; Fadillah, Nurul; Anggraini, Selfi Dwi; Zuhro’ Fitriana, Ani Qotuz (CV. ITTC INDONESIA, 2023)
This research contains various conflict management strategies and the factors that cause the problem of teenage children's openness to parents. This study aims to determine the factors that cause the problem of children's self-disclosure, by knowing these factors it is hoped that teenagers and parents can evaluate these causes. So that this problem does not occur. The research method used in this research is descriptive qualitative. Descriptive qualitative research is a type of research that aims to understand and provide a picture, description, explanation, and a deeper understanding of a problem by studying individuals, groups, or certain events to the fullest. With data sources using interview techniques.